Understanding population genetics - Säll, T.; Bengtsson, Bengt Olle (2017)
"The reader is taken through ten mathematical derivations that lead to important results, explaining in a hands-on manner the key concepts and methods of theoretical population genetics. The derivations are carefully worked out and easy to follow. Particular attention is given to the underlying assumptions and the mathematics used. The results are discussed and broadened out with relevant current implications. All topics feature questions with helpful answers"--Provided by publisher.
Keywords: Genetics, Population